The Monadic Processor - Almeida, Felipe Afonso de (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1994: Anais do VI Simpósio Brasileiro de Arquitetura de Computadores e Processamento de Alto Desempenho, 1994)
In a straightforward pipelined implementation of the Explicit Token Store dataflow model there is an imbalance concerning the execution of dyadic instructions (instructions with two input operands). This is due to the fact that two tokens need to be processed for a dyadic instruction, before valid operands are available to be processed by the Arithmetical-logical Unit, which at each pipeline cycle can consume two tokens and produce as a result also two tokens. In this work we investigate an approach to increase the Arithmetical-logical Unit utilization rate in dataflow processors based on the Explicit Token Store model. We propose an abstract realization of this model where there is two tokens queues. One token queue keeps tokens headed for monadic instructions (instractions with a single input operand). These tokens are utilized whenever the main path of the processor pipeline (feeded directly by the two token queues) is unable to produce valid operands for the Arithmetical-logical Unit to process. Therefore, increasing the utilization rate of the Arithmetical-logical Unit. The other token queue holds tokens headed for dyadic instructions (instructions with two input operands).